Pelatihan Pemanfaatan Aplikasi Genially Sebagai Media Pembelajaran Inovatif Berbasis Digital Bagi Guru SMP Negeri 6 Inamosol, Seram Kabupaten Bangian Barat - Susan E Manakane; Anelia Wlary; Jenny Koce Matitaputty (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Training on the utilization of the Genially application as an innovative digital-based learning media for teachers at SMP Negeri 6 Inamosol, West Seram Regency, is an important initiative in improving the quality of education in the region. The training method consists of 3 steps, namely preparation (correspondence and coordination and needs analysis), implementation (socialization and training/practical and mentoring) and evaluation (testimony and post test). The training participants consisted of 10 people. The results showed that the training participants were very enthusiastic and able to create a variety of learning media with the Genelly application. This was also evident from the testimonials of 10 teachers who felt that the topics given were very interesting, and the training material for developing digital-based learning media with the Genelly application as a medium in the teaching and learning process was very useful. With this training, it is expected that teachers will become agents of change in improving the quality of education in West Seram Regency through the effective use of digital technology.